Flow Injection Spectrophotometric Determination of Histamine in Fish Meals - Abdullah, Mohammad S.; Fakhri, Nabil A. (Science Journal of University of Zakho, 2013)
The study describes flow injection spectrophotometric methods for the determination of histamine in fish and fish meal samples. The methods were based on diazotization of p-toluidine and p-nitroaniline and subsequent coupling with histamine in alkaline medium. The calibration graph with diazotizated p-toluidine gives a linear range from 3.0 to 25.0 µg/ml with correlation coefficient 0.9967, while diazotization of p-nitroaniline and coupling with histamine gives a linear range from 0.5 to 22.0µg/ml with correlation coefficient 0.9985and detection limits 1 µg/ml and 0.3 µg/ml respectively. The effect of common amino acids and some ions on the determination of histamine was examined. Amberlite resin (weak cation exchanger) was used for the removing of histamine from interferences. The recommended FI procedures were successfully applied to the quantitation of histamine in 5 commercial fish meal products after appropriate sample treatment.